Bone conduction hearing implants (BCHIs); life-changing surgery. A quality of life (QoL) study reporting the impact of BCHI surgery on 163 patients’ well-being - Rachael Collins; Ian Nunney; Junaid Hanif; John S Phillips; Amanda Collett (BMJ Surgery, Interventions, & Health Technologies)
Objective This study aimed to review the impact of bone conduction hearing implants (BCHIs) surgery on patients’ quality of life (QoL) across general, physical, social and overall well-being domains.Design A prospective correlational study.Setting Single tertiary referral center in the UK.Participants All adult patients undergoing their first BCHI over a 10-year and 6-month period (between June 1, 2012, and December 31, 2022). A total of 163 were included out of 195 potentially eligible participants.Main outcome measure The Glasgow Health Status Inventory (GHSI) was used to assess patients’ QoL pre and post BCHI surgery.Results BCHI surgery showed significant improvements across all GHSI QoL domains; total (p<0.0001), general (p<0.0001), social (p<0.0001) and physical (p<0.0001).Conclusion The largest of its kind, this study recognizes the wide-reaching impact of BCHIs on patients’ QoL, evidencing them as a highly effective and life-improving surgical intervention.